2018
DOI: 10.1177/1049732318786482
|View full text |Cite
|
Sign up to set email alerts
|

“I Don’t Like Being That Hyperaware of My Body”: Women Survivors of Sexual Violence and Their Experience of Exercise

Abstract: The experience of exercise among women survivors of sexual violence is a multifaceted phenomenon. In effort to inform treatment interventions, we used a phenomenological approach to describe the lived experience of exercise among women survivors of sexual violence. Data analysis from a focus group discussion and individual interviews with eight women survivors receiving services at a rape crisis center (RCC) revealed four themes: exercising (and not exercising) fosters safety, exercising is risky, past trauma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…This result emphasizes an important sex-specific difference between men and women with histories of SV in their perceptions of exercise environments. Previous work has repeatedly shown that exercise environments are often unfriendly toward women with histories of SV (Giles & Darroch, 2014; Pebole, Hall, et al, 2021; Smith-Marek et al, 2018). Yet, results here did not corroborate this finding among men, meaning that exercise professionals may have more flexibility in identifying acceptable places for men with histories of SV to exercise when compared to women with histories of SV.…”
Section: Discussionmentioning
confidence: 99%
“…This result emphasizes an important sex-specific difference between men and women with histories of SV in their perceptions of exercise environments. Previous work has repeatedly shown that exercise environments are often unfriendly toward women with histories of SV (Giles & Darroch, 2014; Pebole, Hall, et al, 2021; Smith-Marek et al, 2018). Yet, results here did not corroborate this finding among men, meaning that exercise professionals may have more flexibility in identifying acceptable places for men with histories of SV to exercise when compared to women with histories of SV.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenological study described the experience and meaning of exercise among women survivors of SV 1. Eight women who identified as survivors of SV and participated in an all-women integrative yoga group offered by a rape crisis centre (RCC) were recruited by purposive sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Although the benefits of NP interventions are known in mental health disorders, little research has been conducted on their risks and benefits for recovery from SV. This study1 describes the benefits and risks of exercise and yoga as experienced by the survivors of SV.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…If interoception is an important factor in SUD and recovery from SUD, then it is important to consider the implication for the significant subset of SUD individuals with co-morbid Post-Traumatic Stress Disorder (PTSD). Bodily attention appears to be relevant to the pathology of trauma-linked disorders, which includes intrusive memories and cognitions that may involve, or be triggered by interoceptive sensations and bodily awareness (Borgmann et al, 2014; Jung and Steil, 2013; Price, 2007; Smith-Marek et al, 2018). In line with these behavioral observations, PTSD and sexual trauma have previously been associated with altered brain metabolism in regions associated with interoceptive and somatosensory processing.…”
Section: Introductionmentioning
confidence: 99%